Violations of concealment of economic activities in the Saudi Legal - Daghriri, Waleed Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The Saudi regulator was keen to combat everything that affects its national economy, including violations of concealment, which are committed with collusion between the concealed and the concealed, so he stipulated the images of their commission, cases of absence, and the penalties prescribed for the perpetrators, and in this research will be shed light on the statement of the images of committing violations of concealment of economic activities and their regular penalties, which came scattered in the folds of the legal and its executive regulations, and collected in this context.In this research, it relied on the inductive and analytical approach, so that the texts of the anti-concealment legal and its executive regulations are extrapolated, and then extracted pictures of these violations from their folds, and showed what they are, how they were committed and their provisions, and the penalties prescribed for the perpetrators, represented in the financial fine and the closure of the economic establishment.The forms of these violations are summarized in enabling non-Saudis to deposit the revenues or profits of economic establishments to their personal accounts, or in their direct financing of those establishments or any of their economic activities, or in granting them higher administrative powers to manage economic establishments, or enabling them to acquire commercial papers, contracts, or blank signed documents, or granting them the right to declare profits to partners, or using bank accounts that do not belong to it. The research came out with a set of important results, which aim to detect and clarify these violations, and the research included a set of recommendations, which aim to address these violations, and reduce their spread.
Keywords: infractions; concealment; activities; economic; anti-concealment legal